Model of Social and Environmental Accountability Based on the Tri Hita Karana Concept in Village Credit Institutions in Bali - Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi; Vol 34 No 5 (2024)DO - 10.24843/EJA.2024.v34.i05.p12, 2024)
This research aims to determine social environmental accountability at Village Credit Institutions (LPD) in Bali based on the Tri Hita Karana (THK) cultural concept. Through an interpretive paradigm, data is collected using documentation techniques, in-depth interviews and direct observation. Qualitative analysis techniques using ethnographic methods are used to reduce data, present and conclude data, and make meaning of it. Social environmental accountability with the THK cultural concept in the aspects of parahyangan, pawongan and palemahan has been implemented through harmonization of relationships between the three aspects of THK. The implications of this research are that it is hoped that harmonization of the relationship between these three aspects can be implemented both internally and externally at the institution. Harmonization of these relationships is implemented by the LPD both internally and externally at the institution. So social environmental accountability in LPD in Bali has a "Harmony" model. Keywords: Environmental social accountability; Tri Hita Karana; LPD